The integrated health service model: the approach to restrain the vicious cycle to chronic diseases - Netsanet Fetene Wendimagegn; Marthie Bezuidenhout (BMC, 2019)
Abstract Background In life time, nearly each person succumbs to some sort of chronic disease and many develop complicated chronic diseases. It is critical to focus on preventive services with a relatively high health impact and favorable cost effectiveness. During routine health facility visits, it is advisable to evaluate both symptomatic and asymptomatic patients for their needs of health promotion and disease prevention services. This necessitates the development of an integrated health service (IHS) approach that incorporates health promotion, disease prevention and curative services. Methods There were two phases for the study. The first phase explored the degree of promotive and preventive health care delivery at the health centers and hospitals. Phase two, utilizing the Delphi strategy, centered on looking for agreement on the finding from phase 1 and on IHS approach. Delphi questions were created based on the results of phase 1, and the reply choices were tied to a five point Likert scale. Consensus was considered come to when 75% of the experts concurred on an issue. From that point, advance clarification and agreement was looked for by implies of a second-round assessment for scores between 50 and 75%. Agreement on proposed IHS model, application of case finding and Periodic Health Examination (PHE) approaches were also sought. This study focuses on finding from phase 2. Result Of the twenty experts, 90% (n = 18) agreed that the IHS framework shows the causal relationship of diseases and included plausible intervention approaches. Experts reached consensus (90%;n = 18) that case finding testing,screening patients for conditions other than the medical care they sought at a particular time, can be performed at health facilities. All experts (100%; n = 20) recommended conducting periodic health examinations in selected diseases for patients who are apparently not sick. Conclusion The Integrated Health Service (IHS) framework was agreed by experts to be a plausible method in describing the causal relationship of chronic non-communicable, communicable, and nutrition-related diseases. The framework can play a vital role by preventing the acquiring, progression, suffering or dying from diseases through restraining the vicious cycle of chronic diseases.